RBA monetary policy communication: The response of Australian interest rate futures to changes in RBA monetary policy - Smales, Lee (Elsevier, 2012)
This paper examines the Australian interest rate futures market reaction to changes in Reserve Bank of Australia (RBA) monetary policy. Having determined market expectations from 30-day Interbank futures, the study finds evidence that interest rate futures react strongly to target rate announcements across the maturity spectrum, with a stronger reaction evident in short maturity futures. Further, there is evidence of an asymmetric news effect whereby volatility reacts more strongly to bad news. Disaggregation of the market reaction into target- and path-surprise factors demonstrates that the change in market expectations of future target rates plays a significant role in explaining changes in yield, particularly for bond futures. There is strong evidence that monetary policy statements drive the path-factor, while the December 2007 modification in policy communication has improved the ability of the RBA to influence market expectations.